A PROSPECTIVE, OBSERVATIONAL STUDY OF PREOPERATIVE GASTRIC CONTENTS AND GASTRIC VOLUME AMONG ADULT PATIENTS SCHEDULED FOR ELECTIVE SURGERY USING BEDSIDE ULTRASOUND (Asian Journal of Medical Research and Health Sciences, 2026)
Background and Objectives: Adequate fasting period according to the fasting guidelines and a normal, predicted gastric emptying period are the prerequisites before the anesthesia induction to avoid pulmonary aspiration (PA). Gastric emptying period can be altered in systemic disorders like diabetes mellitus (DM), chronic kidney disease (CKD), hypothyroidism etc. PA can be a serious perioperative complication associated with significant morbidity and mortality. To avoid these consequences it is better to be thorough of gastric contents and its volume preoperatively. There are radiological aided studies assuring if the fasting period can clear the gastric contents or not. Recently there are literature showing the advantage of ultrasonographic (USG) detection of gastric contents in antrum and to correlate it with gastric emptying time after different kind of food intake. But there are limited studies to know the effect of adequate fasting period in gastric antrum, especially in the patients associated with the comorbidities delaying the gastric emptying. The primary objective of the study is to examine the type of gastric contents after fasting period and to determine if there is variation of gastric contents with the associated comorbidities among fasting patients posted for elective surgery by using bedside ultrasound. The secondary objective is to assess if there is any correlation between fasting time and estimated gastric volume. Methods: The study was conducted in 80 adult patients aged between 18 to 60 years of age belonging to ASA class I, II, III optimized with comorbid diseases posted for elective surgery. A thorough history was taken. The presence of any comorbidities were noted and the fasting period for solids and liquids were noted. A preoperative bedside gastric ultrasound scan was done in supine and right lateral decubitus (RLD) position. Gastric content was noted and cross sectional area (CSA) was measured at the level of gastric antrum in (RLD) position if the content was liquid. Through this CSA gastric volume was derived. Data was collected, tabulated and then analyzed. Results: Among 80 patients; the gastric antrum was empty in 25(31.25%), liquids 1.5ml/kg body weight in 11(13.75%), semisolids in 11(13.75%) and solids in 4(5%) of patients. Different comorbidities were present among 48% and it was absent in 32% patients. The association of comorbidities like DM, CKD, hypothyroidism, ischemic heart disease and obesity with the risk of aspiration was significantly very high. There was weak correlation between the fasting period and estimated gastric volume. Conclusion: Our study showed that fasting more than 6 hours do not guarantee an empty stomach. Patient with co morbidities appear to have significantly high risk for aspiration as compared to those with no comorbidities.